Opportunities and Challenges in Transforming into an Industry-Oriented Local Wisdom Tourism Village - Syafi'i, Muhammad; Syaflita, Dina; Putra, M. Jaya Adi (KnE Social Sciences, 2024)
Tourism based on local wisdom serves as a solution to enhance economic aspects while considering the sustainability of cultural and natural aspects. Industrial tourism can also be packaged to attain environmental and economic benefits. These two tourism themes can be combined in certain areas with potentiality. The aim of this research is to identify the opportunities and challenges of Sering Village in its transition to a local wisdom-based industrial-oriented tourism village. This research adopts a descriptive qualitative approach. The case study’s location of this research is Sering Village, Pelalawan Regency, Riau Province, Indonesia. Data gathering methods include observation, interviews, and documentation. Data analysis methods involve the utilisation of the Miles and Huberman model. The results of this study provide an overview of the opportunities and challenges in developing Sering Village into a local wisdom-based industrial-oriented tourism destination. The prospects held by Sering Village stem from the local wisdom of its community and its strategic location. Sering Village possesses local wisdom preserved by its community in the form of local products as well as traditional activities and customs. In terms of its location, Sering Village is situated between the center of the paper and pulp industry and the Istana Sayap, a legacy of the Malay Pelalawan Kingdom. Istana Sayap can be reached via both land and river routes. However, challenges faced by Sering Village involve public facilities and the absence of a well-conceived model for the development of a local wisdom-based industrial-oriented tourism village in Sering Village. Keywords: local wisdom; industry-oriented; transformation; tourism village